Sugarcane Ratoon Yield and Soil Phosphorus Availability in Response to Enhanced Efficiency Phosphate Fertilizer - Oliveira, Clayton Luís Baravelli de [UNESP]; Cassimiro, Juliana Bonfim; Lira, Maikon Vinicius da Silva; Boni, Ariele da Silva [UNESP]; Donato, Natália de Lima [UNESP]; Reis, Roberto dos Anjos; Heinrichs, Reges [UNESP] (MDPI, 2022)
The low availability of phosphorus in most Brazilian soils causes a heavy dependence of agricultural production on phosphate fertilizers, which are generally agronomically inefficient in tropical soils. Breeding for increased longevity of sugarcane ratoons is extremely important, but understanding how the efficiency of phosphate fertilization can be improved is equally necessary. The objective of this research was to evaluate the effects of phosphate fertilizers with and without polymer coating on the productivity and nutritional status of sugarcane ratoons and phosphorus availability in the soil. The experiment was carried out on a commercial sugarcane field on a dystrophic Ultisol over two growing seasons in a randomized complete block design with four replications. Two phosphorus sources (monoammonium phosphate (MAP) and MAP + Policote) were tested at four rates (20, 40, 60 and 80 kg P2O5 ha−1) in addition to the control (no P fertilization). The Policote-coated phosphate fertilizer induced higher stalk and TRS yields in the first experimental year, while the same effect was not observed in the second year. Nevertheless, with the reapplication of the treatments in the second study year, the mean stalk yield was high in response to the application of 20 kg P2O5 ha−1 of coated fertilizer and very different from that of the higher rates of the same fertilizer, which yielded 88 Mg ha−1, i.e., 8 Mg ha−1 more than the mean of the other rates.
Keywords: phosphorus; Policote; polymers; Saccharumspp